The Effect of Using Flash Cards to Improve Arabic Vocabulary Skills at the Al-Azhar Roudlotul Muttaqiin Islamic Boarding School, Malang/ أثر استخدام بطاقة الالفلاش لترقية إتقان مفردات اللغة العربية في المعهد الأزهر روضة المتقين مالانج - himmatul mardiah; Muhammad Alfankarim Romadoni; Elly Miftahul Rohmah; Laily Fitriani (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2022)
The use of flashcard learning media is expected to improve students' mastering of Arabic vocabulary.  flashcards have the following features (1) Flashcards are effective picture cards, (2) Has two front and back sides, (3) the Front side contains pictures, (4) the Back side contains definitions, picture captions, answers, (5) Simple and easy to make. This study aims to determine the effect of flashcard media on Arabic vocabulary mastery. This study uses a quantitative approach to the type of experimental research. Room A experimental group room B is the control group. Data was collected by test techniques and documentation. Instrument Test Data Analysis, Prerequisite Test namely Normality Test Homogeneity Test and Hypothesis Test. The sig value is obtained. (2-tailed) of 0.014 then Hα is accepted. That there is an effect of the use of flash card media on the Arabic vocabulary skills of students at Al-Azhar Roudlotul Muttaqiin. This research is expected to be used as a reference and can be used and then developed into four skills, namely: listening, speaking, reading, and writing.